Logos em luta : diálogos como artifício literário no Quarto Evangelho - Vito, Francikley (2015)
The fourth biblical Gospel – called Gospel according John – is one of the gospels that have more received analyzes and comments in the entire history of the Christian Church. In this work we intend to take a reading of the Fourth Gospel by the literary bias, considering the narrative elements present in it. Among the present elements in the narrative of the work training, we will look more closely for dialogue on the understanding that it have a device widely used by the narrator in order to make known the identity of Jesus as the Logos - the Word of God. As theoretical support will be useful in the work developed by Robert Alter (2007) and, for a theory about dialogue as a literary device to build the identity of Jesus, we will use the Mikhail Bakhtin’s (1895-1975) philosophical theory of language. In his work on speech and language, Bakhtin understood that all dialogue constituted as an "arena" in which opposing ideologies were put into the fight for the dialogue partners. Observing how this happens, we will analyze two dialogues of the Fourth Gospel: The dialogue between Jesus and Nicodemus (John 3) and the dialogue between Jesus and a Samaritan woman (John 4). The two sections were chosen because in them the dialogues are constituted as the most significant part of the narrative. Thus, the study aims to examine the identity of Jesus is built by the struggle between opposing ideologies in dialogue arena.